Synthesis and characterization of manganese-modified black TiO2 nanoparticles and their performance evaluation for the photodegradation of phenolic compounds from wastewater - Irfan, M. (MDPI, 2021)
The release of phenolic-contaminated treated palm oil mill effluent (TPOME) poses a se-vere threat to human and environmental health. In this work, manganese-modified black TiO2 (Mn-B-TiO2) was produced for the photodegradation of high concentrations of total phenolic compounds from TPOME. A modified glycerol-assisted technique was used to synthesize visible-light-sensitive black TiO2 nanoparticles (NPs), which were then calcined at 300 Â°C for 60 min for conversion to anatase crystalline phase. The black TiO2 was further modified with manganese by utilizing a wet impregnation technique. Visible light absorption, charge carrier separation, and electronâhole pair recombination suppression were all improved when the band structure of TiO2 was tuned by pro-ducing Ti3+ defect states. As a result of the enhanced optical and electrical characteristics of black TiO2 NPs, phenolic compounds were removed from TPOME at a rate of 48.17, which is 2.6 times higher than P25 (18). When Mn was added to black TiO2 NPs, the Ti ion in the TiO2 lattice was replaced by Mn, causing a large redshift of the optical absorption edges and enhanced photodegra-dation of phenolic compounds from TPOME. The photodegradation efficiency of phenolic compounds by Mn-B-TiO2 improved to 60.12 from 48.17 at 0.3 wt Mn doping concentration. The removal efficiency of phenolic compounds from TPOME diminished when Mn doping exceeded the optimum threshold (0.3 wt). According to the findings, Mn-modified black TiO2 NPs are the most effective, as they combine the advantages of both black TiO2 and Mn doping. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.